A methodological framework for the implementation of urban living lab on circular economy co-design activities - Innella, Carolina; Ansanelli, Giuliana; Barberio, Grazia; Brunori, Claudia; Cappellaro, Francesca; Civita, Rocco; Fiorentino, Gabriella; Mancuso, Erika; Pentassuglia, Rocco; Sciubba, Luigi; Zucaro, Amalia (Frontiers in Sustainable Cities, 2024)
Circular Economy (CE) has the potential to tackle many of the challenges we are facing nowadays. It represents nothing less than a paradigm shift, as closing and shortening material loops means adopting completely new ways of producing and consuming. In the European Union, CE is a key strategy to achieve climate neutrality target by 2050, to face the biodiversity crisis, to guarantee economic growth and social wellbeing, within planet boundaries, in accordance with the UN Sustainable Development Goals. Stakeholders' engagement is a crucial point of the transition pathway based on a systemic approach through a co-creation process. Urban areas are the main field of the circular transition process in which all the urban actors, i.e. public institutions, academic and research bodies, economic operators, citizens and civil organizations, are involved. An effective operational tool to realise stakeholders' involvement and co-creation processes is the methodological approach of Urban Living Labs (ULLs). Although ULLs have already been tested and implemented worldwide, there is no description of a stepby-step methodology to implement ULLs aimed at co-creation of project ideas on CE, to be realised in a specific territory. This paper aims to define a methodological framework for implementing ULLs focused on co-designing CE activities. The proposed methodology is based on four main phases: (i) scouting and analysis of the territorial context, (ii) listening and exploration, (iii) participation, (iv) execution. A detailed description of each phase as well as the first application of this framework in different urban communities are presented.